2017
DOI: 10.21303/2504-5695.2017.00421
|View full text |Cite
|
Sign up to set email alerts
|

Study of Food and Energy Values of New Gingerbread Types

Abstract: The article deals with directions of the increase of the food value and decrease of the energetic value of gingerbread products. The results of the studies of the chemical composition of gingerbread products with food additives and changes in their composition were considered. The perspective of the use of vegetable additives in gingerbread technologies was substantiated on the base of the analysis and generalization of theoretical, experimental data and production studies, and the possibility of their use wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Research methods -organoleptic, structural and mechanical, physical and chemical methods with the use of informational computer technologies and software [21]. c -phyto-powder made from roots of snakeweed…”
Section: Research Materials and Methodsmentioning
confidence: 99%
“…Research methods -organoleptic, structural and mechanical, physical and chemical methods with the use of informational computer technologies and software [21]. c -phyto-powder made from roots of snakeweed…”
Section: Research Materials and Methodsmentioning
confidence: 99%
“…There are studies reported by scientists in [12] that are related to increasing the biological value of gingerbread by using natural supplements. It was theoretically substantiated and experimentally confirmed that it was appropriate to apply plant supplements in the manufacture of such products.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…They contain fat as 4 g -10g for 100 g. Carbohydrates are from 9g to 39 g for 100 g of meals [10]. At that the main part of them is food fibers [11,12].…”
Section: Introductionmentioning
confidence: 99%